AN OVERVIEW OF CHARACTERISTICS OF MOBILE AD HOC NETWORKS - Madhu, Vidhiya; S.K.M, Sriee (IJRDO -Journal of Computer Science Engineering, 2017)
Mobile Ad Hoc Networks (MANETs) is a group of multi hop wireless mobile nodes, dynamic topology and infrastructure less connectivity in nature. Constructing a protected protocol for Mobile Ad Hoc Network is a difficult task. There are several protocols planned for secure routing in MANETs, and there is a hybrid routing protocol and it is a group of both proactive and reactive routing method in MANETs. The accomplishment of proposed protocol is based on the clustering technique in Routing. Routing Disorder [RD] attack is the major issue in MANETs, clustering can provide a basis for the safe contact between